CONTRIBUTION TO SELECTION IN VOLLEYBALL - Budimir Bijelić; Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The aim of making selection in volleyball is to determine on a precise basis rate of selectivity as a starting point to gain successful involvement of young population in training, which can greatly help them in a subsequent stage to "clear their way" for high sports achievements. So, the imperative is to select young talented sportsmen who are surely predisposed for sports and who can, provided that they are properly instructed and trained, achieve high scores. 74 female volleyball players, playing for some local teams, age 10 - 17, have undergone testing for determining of thei actual physical height in oreder to estimate their ultimate height levels. The test results obtained from the random sampling showed that for 12,16 % of the female volleyball players ultimate height of above 185 cm is expected what is advantageous for achieving good sports development and high rank competions; 32,43 % of them are expected to reach height levels between 175 and 185 cm what is promising for improving their personal abilities in medium-rank team competitions, while the remaining 55,41 % are expected to reach ultimate height less than 175 cm what may seriously restrain them in proper physical development or out playing in volleyball games.